Effectiveness of a scaled up physical activity intervention in Brazil: A natural experiment - Simões, Eduardo J; Hallal, Pedro C; Siqueira, Fernando V; Schmaltz, Chester; Menor, Danielle; Malta, Deborah C; Duarte, Hebe; Hino, Adriano Akira; Mielke, Gregore I; Pratt, Michael; Reis, Rodrigo S (Preventive medicine, 2017)
Physical inactivity causes 5.3 million deaths annually worldwide. We evaluated the impact on population leisure-time physical activity (LTPA) of scaling up an intervention in Brazil, Academia das Cidades program (AC-P). AC-P is a health promotion program classified as physical activity classes in community settings which started in the state of Pernambuco state in 2008. We surveyed households from 80 cities of Pernambuco state in 2011, 2012 and 2013, using monitoring data to classify city-level exposure to AC-P. We targeted 2370 individuals in 2011; 3824 individuals in 2012; and 3835 individuals in 2013. We measured participation in AC-P and whether respondents had seen an AC-P activity or heard about AC-P. We measured LTPA using the International Physical Activity Questionnaire. We estimated the odds of reaching recommended LTPA by levels of exposure to the three AC-P measures. For women, the odds of reaching recommended LTPA were 1.10 for those living in cities with AC-P activity for less than three years, and 1.46 for those living in cities with AC-P activity for more than three years compared to those living in cities that had not adopted AC-P. The odds of reaching recommended LTPA increased with AC-P participation and knowledge about AC-P. AC-P exposure is associated with increased population LTPA. Extending AC-P to all cities could potentially impact non-communicable diseases in Brazil. •Academia das cidades program (AC-P) may increase physical activity in communities.•Women's leisure-time physical activity odds are significantly higher in AC-P-cities.•Leisure-time activity odds rises 1.46 times for women living 3+year in AC-P cities.•Leisure-time activity odds rises between 1.6 and 9.0 times for AC-P participants.•Hearing or seeing AC-P increases the odds of being active in leisure-time by 50%.